THE ANALYSIS OF CREDIT RISK EFFECT ON BANKâ€™S PROFITABILITY AT PT. BANK CENTRAL ASIA, Tbk - Rosanti, Twike Elfira (Jurnal Ilmiah Mahasiswa FEB, 2018)
The purpose of this study are 1) To describe the ratio of CAR, LDR, BOPO and NPL have an effect on bank profitability either partially or simultaneously at PT. Bank Central Asia, Tbk 2) To describe the dominant factor affect bank profitability at PT. Bank Central Asia, Tbk. The type of research conducted is explanatory research (explanation) ie the researcher explains the causal relationship between the variables through hypothesis testing. Techniques used in collecting data is done through documentation. Data analysis methods to determine the effect of CAR, LDR, BOPO and NPL ratio to bank profitability either partially or simultaneously at PT. Bank Central Asia, Tbk is used multiple regression method with data panel model and as data processing tool using Eviews 7 program.Based on the results of research and discussion that has been done then can be drawn conclusion as follows: 1) Ratio of CAR, LDR, BOPO and NPL have an effect on bank profitability either partially or simultan at PT. Bank Central Asia, Tbk. 2) Based on the analysis results can be seen that the CAR has a regression coefficient of 0.409551, LDR of 0.144030, BOPO of 0.144030 and NPL of 0.103040. Based on the results of the comparison shows that CAR has the greatest influence on bank profitability at PT. Bank Central Asia, Tbk.Â  Keywords: CAR, LDR, BOPO, NPL, and PROFITABILITY BANK